Relationship between qualitative characteristics of data extracted from accounting information systems and E-commerce in warehouses of Iranian petrochemical industry - Badran Badrani, Safieh Siadat, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The present study aims to investigate the relationship between qualitative characteristics of accounting information extracted from e-commerce and accounting information systems in warehouses of the Iranian petrochemical industry. This is an applied study in terms of purpose and a descriptive-analytical survey in terms of the data collection method. The statistical population includes all 150 financial and senior managers of all 50 petrochemical companies in the city of Assaluyeh. Sampling was not performed due to the limited number of population subjects. For this purpose, 180 questionnaires were distributed, of which 144 were returned and finally, after the reviews, 136 questionnaires were accepted to be used in data analysis. SPSS v.18 was used for statistical analysis of the data obtained from the questionnaires. Finally, the results showed that in the petrochemical industries of Iran, there is a significant relationship between the qualitative characteristics of accounting information extracted from e-commerce and accounting information systems. There is also a statistically significant relationship between effectiveness, quality, timeliness, and comparability of information extracted from the risk control e-commerce and accounting information system. On the other hand, in this industry, there is no statistically significant relationship between the usefulness and reliability of information extracted from the e-commerce customer satisfaction and accounting information system.